Turkey : Report on Observance of Standards and Codes; Data Module, Response by the Authorities, and Detailed Assessment Using the Data Quality Assessment Framework (DQAF). - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This report examines the Observance of Standards and Codes on the Data Module for Turkey. Progress in data quality reflects the authorities' commitment to set statistical development on a high and sustainable path, and to address remaining challenges. A cornerstone of this effort is the more robust framework established by the new Statistics Law of Turkey of November 2005. This law assigned compilation responsibilities for a broad range of official data, including macroeconomic statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet